STUDENTS' ANXIETY LEVEL IN PUBLIC SPEAKING AND THEIR INVOLVEMENT IN ORGANIZATION - Pane, Widi Syahtia (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2023)
Public Speaking is one of skill that should be possessed by a pre-service teacher, especially English teacher. In IAIN Samarinda, the students get two semesters of this Public Speaking class, which are semester 3 and semester 4. KKI class in one of special class in IAIN Samarinda which the class are as level as international class. This study tried to reveal the level of students’ anxiety level in public speaking and students’ involvement in organization, and whether they are affecting to each other. This study used qualitative as the method and it used students interview and also students’ score in doing public speaking activities as instruments. The result showed that students who join organization tend to have better confidence and students who do not join any organization tend to have more level of anxiety. Despite of that some students from this group manage to do better performance in public speaking. It then revealed that even they do not join any organization, many aspects affect the good performance as well.